1990
DOI: 10.1111/j.1467-1770.1990.tb01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Language‐Learning Strategies in Monolingual and Multilingual Adults*

Abstract: This study investigated the hypothesis that people with multiple language skills have different language‐acquisition strategies than do people with single language skills. Multilingual and monolingual subjects learned a miniature linguistic system incorporating a reference world under instructions to “memorize” or instructions to “discover rules”. Although there was no clear evidence that multilinguals were superior in language learning abilities overall, multilingual subjects were found to be more able to adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(122 citation statements)
references
References 13 publications
8
100
4
Order By: Relevance
“…However, whether this suggests that aptitude itself is trainable or whether it is test performance that is affected remains an open question and one that would be difficult to empirically address. Nayak, Hansen, Krueger and McLaughlin (1990) suggest that multilingual learners are more adept at using strategies in taking the tests rather than being more successful overall, and this may be the case with our participants as well.…”
Section: Research Question 2: L2 Statusmentioning
confidence: 81%
“…However, whether this suggests that aptitude itself is trainable or whether it is test performance that is affected remains an open question and one that would be difficult to empirically address. Nayak, Hansen, Krueger and McLaughlin (1990) suggest that multilingual learners are more adept at using strategies in taking the tests rather than being more successful overall, and this may be the case with our participants as well.…”
Section: Research Question 2: L2 Statusmentioning
confidence: 81%
“…Contrary results of researches on the benefits and drawbacks of bilinguality encouraged some researches (Barik & Swain, 1978;Lambert & Tucker, 1972;Nayak et al, 1990;Magiste, 1984) to conduct researches with more controlled variables. Barik and Swain (1978), and Lambert and Tucker (1972) had conducted experiments in which sex and age were considered as control variables.…”
Section: Introductionmentioning
confidence: 99%
“…Nation and McLaughlin 1986;Nayak et al 1990) evidenced the positive transfer of learning strategies insofar as expert learners outperformed their less experienced counterparts. Later, Kemp (2001) found that the performance of multilingual learners on grammaticality tests depended on the number of languages they knew.…”
Section: Multilingual Strategy Use and Developmentmentioning
confidence: 99%